Electrophoretic deposition of bioglass reinforced zirconia for biomedical application. Issue 9 (9th September 2021) - Zac, C.H.; Bushroa, A.R.; Sarraf, M.; Rizwan, M.; Jamaludin, M.F.
Abstract: Ti‐6Al‐4V alloy is a bioinert material with low bioactive properties, which may hamper its bonding ability with body tissues that can be overcome by coating the metal with a bioactive glass layer, 45S5 reinforced zirconia. This coating can be deposited using an electrophoretic deposition process. In this study, a comparison is made between three types of coatings which are bioglass, pure zirconia and bioglass reinforced zirconia before and after heat treated. Mechanical evaluations using scratch tests and micro‐hardness tests are conducted to evaluate the adhesion strengths and hardness properties of the coatings. The results show the presence of oxygen, and variations in the amounts of bioglass and zirconia, due to the activity of crystallization. X‐ray diffraction confirms presence of all precursor elements in the coatings. The highest hardness value of 414 HV 2.942 is obtained for the sintered bioglass‐zirconia composite coating, as compared to the hardness of bare titanium alloy of 266 HV 2.942. The highest adhesion strength of 1929 mN is also obtained for the bioglass‐zirconia composite coating. These results show excellent performance for sintered bioglass‐zirconia composite coating, making it a potential coating material for biomedical implants. Abstract : A technique of electrophoretic deposition is applied to prepare coatings of bioactive glass 45S5, pure zirconia, and bioactive glass‐zirconia composite. Characteristic of each coating is compared, and their performance are evaluated. The results identify achievement of sintered bioglass‐zirconia composite coating, and suggesting it as a potential coating material for biomedical implants.